EFEKTIVITAS MODEL PEMBELAJARAN PROBLEM BASED LEARNING MELALUI MEDIA PEMBELAJARAN KARTU ANGKA UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP DAN LITERASI MEMBACA PADA SISWA - Putri Yuli Anggraeni; Rida Fironika Kusumadewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study demonstrates that the Problem Based Learning (PBL) model using number card media is effective in improving the mathematical concept understanding and reading literacy of second-grade students at SD Negeri Genuksari 01 Semarang. The one-sample t-test results showed a t-value of 3.697, which is greater than the critical t-value of 2.004 at a 5% significance level, indicating that students have met the Minimum Mastery Criteria (KKM) in mathematical concept understanding. Additionally, the implementation of the PBL model also significantly enhanced students’ reading literacy. The number card media serves as a concrete and interactive learning aid, facilitating students’ comprehension of the material and improving their reading skills. Therefore, the PBL model through number card media is proven to be an effective strategy to support successful learning outcomes in mathematics and reading literacy at the elementary school level.